Trace element composition of organs and tissues of the Caspian seal (Phoca caspica Gmelin, 1788) in the conditions of technogenesis of the biosphere - T. S. Ershova; V. F. Zaitsev; M. Z. Gadzhidadaev; Sh. M. Samudov; V. A. Chaplygin; Yu. A. Shevchenko (Юг России: экология, развитие)
Aim. To identify features of the accumulation and distribution patterns of Zn, Cu, Mn, Cr, Ni, Co, Hg, Cd, Pb in organs and tissues of the Caspian seal.Materials and Methods. Sampling was carried out according to generally accepted methods and the determination of heavy metals was performed by atomic absorption spectroscopy using an atomic absorption spectrometer with electrothermal atomization MGA‐915 MD.Results. In the body of the Caspian seal, zinc, manganese, chromium, cobalt and mercury are mainly deposited in the liver, nickel and cadmium in the kidneys, copper in the stomach and lead in adipose tissue. Under the same living conditions, females have in most cases higher coefficients of accumulation of trace elements than males. Female Caspian seals accumulate more copper, mercury and cadmium than males. Sexual differences in the accumulation of zinc, nickel, cobalt and lead by organs and tissues of the Caspian seal were not detected. With age, the Caspian seal has a significant increase in the concentration of zinc, copper, mercury and cadmium, and the digestibility of manganese, chromium, cobalt and lead decreases.Conclusion. Chemical elements are distributed unevenly in the body of a seal, depending on the properties of metals and the functional features of organs. Significant concentrations of metals are noted primarily in organs that are characterized by active metabolic processes on the one hand, and on the other are actively involved in processes aimed at maintaining homeostasis.